2016
DOI: 10.1093/socpro/spw006
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Economic Disconnection among Families in the Child Welfare System

Abstract: Children and the intergenerational transmission of poverty Description of Project's Link to Core Thematic Research Area Noted Above: This project focuses on a particularly vulnerable subgroup of poor families with childrenthose who come in contact with the child welfare system. The goal of the project is to discern patterns of family income dynamics-and types of economic disconnection-relative to spells of child welfare involvement and assess the impact of these trajectories on family reunification (versus ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In contrast, financial instability or precarity can have a direct impact on families. Hook and colleagues' (Hook et al 2016) construction of income histories of parents with children in foster care found that two thirds of the N = 15,159 parents had experienced 'economic disconnection' (i.e. without either work or welfare) over a three-year period and these families were also the least likely to achieve reunification with their birth children.…”
Section: Cash Transfersmentioning
confidence: 99%
“…In contrast, financial instability or precarity can have a direct impact on families. Hook and colleagues' (Hook et al 2016) construction of income histories of parents with children in foster care found that two thirds of the N = 15,159 parents had experienced 'economic disconnection' (i.e. without either work or welfare) over a three-year period and these families were also the least likely to achieve reunification with their birth children.…”
Section: Cash Transfersmentioning
confidence: 99%
“…The effects of financial limitations on family reunification are also demonstrated by Wells and Guo [ 29 , 30 , 31 ], who found welfare reforms that reduced the monthly income of parents, slowed reunification. Hook and associates, [ 37 ] concluded that parents with children in out-of-home care had difficulty meeting both the demands of employment and child welfare mandates, which increased stress and added risk factors that again slowed reunification. It is possible that similar problems are faced by parents with children in out-of-home care in Quebec, as they are required to make financial contributions to their children’s out-of-home care needs [ 38 ], which may reduce the income needed to secure basic necessities, increase stress levels, and as a result, delay reunification.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although placement of a child in foster care is a recognized factor influencing children's health, behaviour, and social trajectories, very little has been documented about its consequences on the health and social outcomes of mothers. 2,3 Mothers of these children represent a highly marginalized and growing population of caregivers, who are disproportionately poor, racialized, and likely to have also been in foster care as children. 4,5 Among mothers, Indigenous women experience the highest rates of forced separation from their children, with census data showing Indigenous children comprising over 50% of all children aged 4 years and younger in foster care, while accounting for only 7% of the child population.…”
mentioning
confidence: 99%